GATE, ESE and PSU 2019: engineering maths - Kreatryx (KREATRYX Pub, 2018)
GATE, ESE and PSU 2019: engineering maths / Kreatryx. -- New Delhi: KREATRYX Pub., 2018 153.9451 K92e4 4th ed. No. of Copies : 5